Temperature-responsive and piezoresistive performances of poly(N- isopropylacrylamide)-grafted reduced graphene oxide smart fiber. (5th January 2019) - Ma, Hui; Zhang, Huanxia; Cao, Jianda; Tong, Mingqiong; Zhao, Jianwei; Li, Yifei; Xu, Hong; Wu, Wen
Abstract: In this work, temperature-responsive poly(N-isopropylacrylamide) (PNIPAm) was covalently grafted onto the edge of graphene oxide (GO) sheets through a facial method cross-linked by 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC·HCl) and N-hydroxysuccinimide in aqueous solution at room temperature. Then, the dispersion was wet spun to form a GO composite fiber. Scanning electron microscopy images suggest that severe edge distortions occur in PNIPAm-g-rGO hybrid fibers, indicating the covalent attaching of PNIPAm molecules onto the edge of graphene sheets. The PNIPAm-g-rGO fibers showed more favorable and improved electrical property than the pristine rGO fibers. Moreover, the coil-to-globule transition of the end-grafted PNIPAm chains was partially restricted by graphene sheets in the composite fiber, thereby causing the elevation of the phase transition temperature. Switching test of temperature-responsive versus electrical conductivity function has proved that the observed temperature-induced electrical conversion of the fibers was highly reversible and reproducible. Simultaneously, the composite fiber exhibited higher piezoresistive sensitivity compared with neat fiber. This smart fiber has shown remarkable potential for intelligent strain sensors, textiles, actuators, wires and on/off switches.